Peningkatan Keterampilan Interpretasi dan Infereni dengan Menerapkan Model Pembelajaran Kooperatif Group Investigation pada Materi Asam Basa - Adila Siwinasti Yudawindantika; Utiya Azizah (Universitas Lampung, 2020)
This study aims to describe the implementation of the Group Investigation cooperative learning model and the activities of students to practice critical thinking skills of interpretation and inference on acid-base material. The research method used is the One Group Pretest Posttest Design method to determine an increase in interpretation and inference skills. The trial was conducted on 30 students of class XI MIA SMA 14 Surabaya. The data obtained were analyzed descriptively quantitatively. The results showed that: (1) the use of learning models with cooperative type Group Investigation type 1 to successive closures was 91.67%; 91.67%; 92.71%; 91.67%; 89.59%; 95.83%; and 90.27% with a very good category, (2) the results of students' activities on interpretation and inference skills from meetings 1 to 3 amounted to 17.56%; 15%; and 17,89%, and (3) improved interpretation and inference skills get N-Gain results high category of 93.33%; 86.67% while the medium category 6.67%; 13.33%.